2016
DOI: 10.1002/hed.24292
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor family aberrations as a putative driver of head and neck squamous cell carcinoma in an epidemiologically low‐risk patient as defined by targeted sequencing

Abstract: Background Targeted sequencing of epidemiologically low risk (ELR) HNSCC patients could help identify novel drivers or lost suppressors leading to precision medicine protocols and improved survival rates. Methods An ELR-HNSCC patient was selected for targeted sequencing. We then assessed next generation sequencing cohorts from the Oncomine Powertool Database, which contains pan-cancer data from The Cancer Genome Atlas(TCGA). Results Targeted sequencing revealed FGFR1 amplifications as a putative driver of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

7
3

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…(15,16) In HNSCC, genetic alterations of not only EGFR but also ERBB2, FGFR1, FGFR3, and MET have been reported. (17)(18)(19)(20)(21) RTK gene alterations induce epithelial-mesenchymal transition, (22) allowing tumor cells to acquire migration capabilities. Overexpression of EGFR was demonstrated to be an adverse prognostic factor in HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…(15,16) In HNSCC, genetic alterations of not only EGFR but also ERBB2, FGFR1, FGFR3, and MET have been reported. (17)(18)(19)(20)(21) RTK gene alterations induce epithelial-mesenchymal transition, (22) allowing tumor cells to acquire migration capabilities. Overexpression of EGFR was demonstrated to be an adverse prognostic factor in HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, our analysis found a potential driver amplification of the tyrosine kinase receptor FGFR1 . Extending the discovery to The Cancer Genome Atlas (TCGA) HNSCC cohort, we demonstrated that the FGF/FGFR pathway is dysregulated in >30% of HNSCCs and likely represents a previously unrecognized aberration driving disease pathogenesis [ 10 ]. Consequently, carefully designed studies focusing on the genetics of under-studied epidemiologic populations can be very informative.…”
Section: Introductionmentioning
confidence: 99%
“…no. 111-035-045; Jackson ImmunoResearch, West Grove, PA) secondary antibody at room temperature for 1 hour as described elsewhere (Tillman et al, 2016). The blots were then visualized with chemiluminescence and imaged.…”
Section: Methodsmentioning
confidence: 99%